Financing With Heart And Intelligence: Augmenting Intimacy And Sustainability Through Islamic Fintech - Misyer Tajudin, Rosmini Omar, Anssi Smedlund, Razi Pahlavi Aziz (International Journal of Advanced Science and Technology, 2020)
Efforts by global society to improve financial inclusion amongst the underprivileged have gained traction, but challenges abound to prevent a comprehensive success. Open innovation between critical stakeholders in the emerging fintech industry brings about positive results to improve financing needs of this huge segment of the market that ranges from those underserved by banks because of credit risk, to migrants and refugees. Despite the introduction of disruptive fintech services, the needs generated by unimproved conditions and protracted crises outstrip the resources available to meet them. Islamic fintech has the potential to solve this problem through its mandatory (zakat), voluntary (waqf and sadaqah) philanthropic principles, as well as its encouragement to fostering the culture of science, technology, and advancement, in forming a steady pool of resources to enable financial inclusion. This research employs literature review, conceptual analysis and qualitative case study methodology to provide an overview of how fintech start-ups in Finland and Malaysia facilitate financial inclusion through the illustration of two major fintech sectors, namely e-marketplace/payments and crowdfunding/peer-to-peer (P2P) financing. We synthesize that open innovation further enhances fintech services to elevate social finance from its current infrastructure to a more sustainable outcome-base funding, changing the way capital could be mobilized for social impact. Our findings also suggest that Islamic fintech offers an effective and efficient alternative to raising funds in the backdrop of financing the underserved individuals, while providing a knowledge-based platform that enhances customer-service provider intimacy to guide future social finance decisions.